Measuring the Impact of Content Marketing: Key Metrics and Tools for ROI Analysis - Karimov Abdulaziz Ikromjonovich (European Science Publishing, 2023)
This article delves into the realm of content marketing, investigating its impact through a comprehensive analysis of key metrics and analytical tools for Return on Investment (ROI) assessment. As businesses increasingly invest in content marketing strategies, the need to measure and quantify its effectiveness becomes paramount. Through a systematic exploration of established metrics and cutting-edge tools, this study aims to provide insights into evaluating the tangible outcomes of content marketing efforts. The research underscores the importance of aligning content goals with organizational objectives and employing appropriate measurement techniques to gauge ROI accurately. By examining real-world case studies and utilizing quantitative data analysis, this article offers a holistic understanding of the role that metrics and tools play in deciphering the impact of content marketing on business success.